1999
DOI: 10.1021/jp983681h
|View full text |Cite
|
Sign up to set email alerts
|

Salt Catalysts Containing Basic Anions and Acidic Cations for the Sol−Gel Process of Titanium Alkoxide:  Controlling the Kinetics and Dimensionality of the Resultant Titanium Oxide

Abstract: The sol−gel process from titanium alkoxide monomer to titanium oxide polymer was remarkably enhanced by salt catalysts containing basic anions and acidic cations. An ammonium carbonate catalyst promoted the precipitation of spherical titanium oxide particles at low concentrations of titanium alkoxide and water at room temperature. Dehydrative polycondensation in the sol−gel process involves both deprotonation and dehydroxylation, and the carbonate anion enhanced the deprotonation as a base catalyst while the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 14 publications
4
64
0
Order By: Relevance
“…Chitosan can prevent implantation of E. coli, cells by destroying the bacterial biofilm which protects them from being washed away [14]. The metallic glasses might be capable of the same action within their inhibition zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan can prevent implantation of E. coli, cells by destroying the bacterial biofilm which protects them from being washed away [14]. The metallic glasses might be capable of the same action within their inhibition zones.…”
Section: Discussionmentioning
confidence: 99%
“…Since the post-separation of the powder catalyst in a slurry system is a major impediment in photocatalyst production [9,10], immobilized TiO 2 with high surface area (e.g., porous TiO 2 thin film) is favored for antimicrobial applications [2][3][4][11][12][13][14].…”
mentioning
confidence: 99%
“…The literature reports approaches for the synthesis of nanoparticles of titania, including thermal hydrolysis [17,18], sol-gel [19,20], hydro/solvothermal method [21,22] and microemulsion processes [23,24]. Among them, solvothermal and microemulsion methods are extensively used for the preparation of nanomaterials.…”
Section: -Introductionmentioning
confidence: 99%
“…We have already found that the salt catalyst effectively accelerates the polycondensation of titanium alkoxide. 19,20,22,23 We also report the unique procedure for making a self-standing film of layered titania/isostearate nanocomposite by floating the sol on the water surface, which yields selfstanding films with good transparency and flexibility.…”
Section: Introductionmentioning
confidence: 98%
“…19 Without the deceleration of the hydrolysis, three-dimensional polymerization takes place due to very rapid hydrolysis of the titanium alkoxides. For the formation of layered materials, two-dimensional polymerization is required.…”
Section: Introductionmentioning
confidence: 99%